1988
DOI: 10.1159/000184886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Oral Protein Load on Glomerular Filtration Rate in Healthy Controls and Nephrotic Patients

Abstract: Glomerular filtration rate (GFR), effective renal plasma flow (ERPF) and humoral factors were simultaneously examined before and after a 50-gram oral protein load in 12 healthy controls and 12 nephrotic patients. The protein load led to rises in GFR with unchanged filtration fraction in both groups although the rate of increase in GFR was greater in the former. The levels of blood urea nitrogen, serum osmotic pressure, plasma glucagon and serum insulin, but not plasma angiotensin II, were significantly elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The results of this study support the previous findings that an acute increase in protein intake can stimulate GFR also in patients with diseased kidneys [6,7,9]; moreover, they demonstrate that the hemodynamic changes following a protein load may affect the renal handling of sodium and water. Both these hemodynamic and physiologic changes are apparently blunted by pre treatment with the ACE inhibitor enalapril.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study support the previous findings that an acute increase in protein intake can stimulate GFR also in patients with diseased kidneys [6,7,9]; moreover, they demonstrate that the hemodynamic changes following a protein load may affect the renal handling of sodium and water. Both these hemodynamic and physiologic changes are apparently blunted by pre treatment with the ACE inhibitor enalapril.…”
Section: Discussionsupporting
confidence: 90%
“…Reserve capacity of kidneys was lower at patients with HTN-n in comparison with HTN that is probably caused not only with systemic hypertension, but also with presence of glomerular injury, proteinuria, and other factors. 28 Results of our research do not differ from data of Mizuiri S. et al 23 where 50 g of protein intake increased GFR for 15% at healthy subjects, and it varied from 0 to 19.4% at nephropathic patients. Age and duration of hypertension are one of the important factors of renal function decline.…”
Section: Discussionsupporting
confidence: 46%
“…21 Many studies demonstrated response of basal GFR to different stimuli from usual chicken and beef meat intake to amino acid and some drugs infusions in healthy individuals. 8,9,[22][23][24][25][26] In our study we first used …”
Section: Discussionmentioning
confidence: 99%
“…Renal functional reserve is thought to be reduced or lost entirely when renal mass falls below a certain limit [7,8]. A lowered renal functional reserve has been reported in patients with nephrotic syndrome [9], IgA-nephritis [7] in patients after nephrectomy [3] and after renal transplanta tion [10,11].…”
Section: Discussionmentioning
confidence: 99%